The Body in the Classroom after Covid-19: An Exercise in Pedagogical Reflexivity - Wiant Cummins, Molly (Critical Education, 2024)
In this essay, I use autoethnography to investigate the multiple adaptations of the (instructor’s) performative body in the classroom, both online and in-person, due to Covid-19. Specifically, attuning to these adaptations makes space for reclamation of the (instructor’s) performative body in pedagogical spaces by re-engaging embodied pedagogy. Through autoethnography, I offer insights on dis/connection in online teaching, especially in an emergency, remote setting; the adaptation necessary to move back to in-person teaching during a pandemic; and a recommitment to acknowledging the identity of bodies that enter pedagogical spaces together. The lessons learned require focus on the power and privilege, both institutional and societal, that instructors and students must navigate in the classroom. Ultimately, through this exploration of the performative body’s adaptations, embodied pedagogy moving forward highlights the possibilities of our classrooms to be places where pedagogical bodies can re-engage one another.